Building ferraris with kancil - UiTM, MITASA (Kesatuan Kakitangan Akademik UiTM (MITASA), 2025)
Oftentimes, when talking about graduate employability, we look at how a big chunk of our local graduates failed to secure jobs due to the same, recurring issues - weak language, poor communication skills, etcetera. These young, polished minds of the country spent a good 3 or 4 years mastering the knowledge, skills and all the art of their trades some with blood and sweat and family fortunes invested - only to get a NO from employers for failing to express and impress with words.